2009
DOI: 10.1215/15228517-2009-007
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of temozolomide plus O6-benzylguanine 5-day regimen with recurrent malignant glioma

Abstract: This phase I clinical trial conducted with patients who had recurrent or progressive malignant glioma (MG) was designed to determine the maximum tolerated dose (MTD) and toxicity of three different 5-day dosing regimens of temozolomide (TMZ) in combination with O(6)-benzylguanine (O(6)-BG). Both TMZ and O(6)-BG were administered on days 1-5 of a 28-day treatment cycle. A bolus infusion of O(6)-BG was administered at 120 mg/m(2) over 1 h on days 1, 3, and 5, along with a continuous infusion of O(6)-BG at 30 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 15 publications
(22 reference statements)
0
28
0
Order By: Relevance
“…Concurrent administration of O 6 BG restores tumor cell sensitivity to alkylating agents such as TMZ, which was previously investigated as a strategy to improve TMZ efficacy in recurrent GBM patients (5,6). However, early phase studies revealed that O 6 BG/TMZ administration caused severe off-target myelosuppression.…”
Section: Resultsmentioning
confidence: 99%
“…Concurrent administration of O 6 BG restores tumor cell sensitivity to alkylating agents such as TMZ, which was previously investigated as a strategy to improve TMZ efficacy in recurrent GBM patients (5,6). However, early phase studies revealed that O 6 BG/TMZ administration caused severe off-target myelosuppression.…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, dose limitation was myelosuppression manifested as neutropenia, leukopenia, and thrombocytopenia [86,89,91,93,94]. That O 6 -BG exacerbated this toxicity provides strong circumstantial evidence for MGMT being a major resistance mechanism, at least in the corresponding normal human bone marrow stem cells.…”
Section: Pharmacokinetic Parameters Of O 6 -Bg and O 6 -Btgmentioning
confidence: 92%
“…Using an O 6 -BG dose of 100 mg/m 2 [86] or 120 mg/m 2 [90], the maximal tolerated dose of carmustine was 40 mg/m 2 , which is considerably lower than the dose of 120 mg/m 2 without the MGMT inhibitor. Using bolus infusion of O 6 -BG (120 mg/m 2 ,1 h) on days 1, 3, and 5, combined with a continuous infusion of O 6 -BG at 30 mg/m 2 /day, the maximal tolerated dose of temozolomide was 200 mg/m 2 on day 1 and 50 mg/m 2 /day on days 2-5 [91]. The total dose (400 mg/m 2 ) was only slightly less than the maximum tolerated dose of a single temozolomide application without MGMT inhibitor, which was 472 mg/m 2 [89].…”
Section: Pharmacokinetic Parameters Of O 6 -Bg and O 6 -Btgmentioning
confidence: 99%
“…Since one molecule of MGMT removes only one alkyl molecule, an excess of DNA adducts at the O 6 -position could completely deplete MGMT [29,30]. The stoichiometric and irreversible transfer of adducts to internal cysteine residues at position 145 prevents GC AT transitions or [41,43,44] Melanoma in vivo [38,39] Pediatric/solid tumors Phase I [45] Glioblastoma A clinical trial [40] Lomeguatrib TMZ Melanoma A clinical trial [52] Prostate, CNS, colorectal cancer A clinical trial [53] Acute leukemia in vitro [49] Pancreatic Phase I [50] Breast cancer in vitro/in vivo [48] Ovarian cancer in vitro [47] Antiepileptic drugs…”
Section: Mgmt Activity Determines Tmz Resistancementioning
confidence: 99%